Design and analysis of flyback micro inverter for integration of fuel cells with single phase grid - Elangovan, D. (IAEME Publication, 2017)
Renewable energy is going to play a major role in the future energy scenario. All the existing topologies use number of intermediate stages before conversion of DC input to the AC output to the grid side. For this type of conversion, efficiency is very low and number of power components are also very high. In this paper, a low cost high efficiency simple DC-AC flyback inverter is proposed. The proposed converter consists of a simple flyback converter followed by a simple full bridge inverter with passive snubber in the primary. The modes of operation of the converter along with the design of the converter with the snubber is discussed. Experimental results from simulations are presented as well. © IAEME Publication.